Risk taking behavior of privatized banks - Mohsni, Sana; Otchere, Isaac (Journal of Corporate Finance, 2014)
We examine the risk taking behavior of privatized banks prior to and after privatization and find that privatized banks experience a significant decrease in risk after privatization; however they continue to exhibit higher risk than their rivals. This finding is consistent with the assertion that following privatization and the removal of government guarantees and subsidies, privatized banks become more prudent. Since rival banks do not experience a significant change in risk taking, we attribute the reduction in risk experienced by the privatized banks to changes in the banks' ownership structure rather than to industry factors. Interestingly, we also find that a higher fraction of the privatized banks' shares sold beyond a certain intermediate level induces higher risk taking, as the privatized bank becomes more accountable to shareholders. The finding that the fraction of shares sold is positively related to risk taking, coupled with the result that the privatized banks had higher risk in the pre-privatization period than in the post-privatization period suggests a nonlinear relationship between government/private ownership of banks and risk taking. Results of further analysis are consistent with a somewhat U-shaped relationship between private ownership and risk taking. The risk taking behavior of newly privatized banks is also influenced by the country's level of development and degree of political risk. Our results are robust to different measures of risk.